THE BARRIER DOOR VISUALIZATION OF GUILTY BOUNDARIES THROUGH A SYMBOLIC APPROACH - Di Odessa, Nigel
Guilt in certain cases can prevent humans from thinking clearly, one of which is caused by certain tragedies that have befallen individuals. Such as childhood trauma due to strict rules, harsh punishments either from groups or individuals around their environment, or experiencing significant failures in life's journey. Experience of events like this example gives rise to excessive guilt which can be self-destructive. This series of works symbolically is able to describe the situation of the mind that is covered by guilt in aspects of human life. Describing the same object from work to work that represents certain aspects of life in the mindset of humans who are disturbed by guilt. It is hoped that this work will be useful for learning that guilt will continue to haunt individuals if humans do not rise from these thoughts. To visualize the feeling of guilt, the writer uses a symbolic approach, namely by using a daily object in the case, a door. This series of works produces a variety of symbolic forms of door with meanings to limit the author's sense of guilt. Besides that, the writer also uses soft pastel medium to describe the writer's guilt. The author uses medium soft pastels because they are able to display motion blur shapes with dark colors. On the other hand, the writer also has a tendency to use everyday items as the writer's visual language. The selected objects will become symbolic visuals that will remain in these works. Motion blur is also present as a visual language which also continues to be present in the works of this series. The success of the work can be proven through how rational representations with objects used as symbols can be thought of. Because the characteristics of the same object with different shapes will bring out different visual characteristics and meanings. Through representation, it is expected to be able to connect and visualize guilt with aspects of human life through a still life object.